Személyes használatra: Egy mongol kéziratcsomag - Kápolnás, Olivér (Távol-keleti Tanulmányok, 2018)
This article explores a small (14 cm×7 cm×1.5 cm) Mongolian manuscript package. The package consists of several manuscripts as follows: 1. incense offering to the Five Personal Protectors (tib. 'go ba'i lha lnga); 2. Diamond sutra; 3. two printed amulets (with Tibetan scripts); 4. a drawing (with Tibetan text on the backside); 5. some pieces of paper with astrological content. We can divide these texts into three parts: protectors, blessers and astrological manuals. The protectors are the offering to the Five Personal Protectors and the amulets. The blesser is the Diamond sutra, which has beneficial effect to the reader or the holder of the manuscript. This manuscript has a colophon that states it was written (or copied) in 1914. The astrological manuals are on different pages that seem to have been used more than the others (the sheets indicate frequent use). In this article, the offering to the Five Personal Protectors is transcribed and translated, the description of the amulets is given and one part of the astrological manual is also presented.